2023
DOI: 10.1101/2023.02.09.527738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A “Four Core Genotypes” rat model to distinguish mechanisms underlying sex-biased phenotypes and diseases

Abstract: Background: We have generated a rat model similar to the Four Core Genotypes mouse model, allowing comparison of XX and XY rats with the same type of gonad. The model detects novel sex chromosome effects (XX vs. XY) that contribute to sex differences in any rat phenotype. Methods: XY rats were produced with an autosomal transgene of Sry, the testis-determining factor gene, which were fathers of XX and XY progeny with testes. In other rats, CRISPR-Cas9 technology was used to remove Y chromosome factors that ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Future studies are needed to determine whether organizational effects of gonadal steroid hormones and/or sex chromosome gene expression differences contribute to the increased female vulnerability in aELS‐induced fear learning in adulthood. One compelling approach to addressing this question would be to use the four‐core genotype rat or mouse model, where chromosomal sex (XX vs. XY) and gonadal hormone status (ovaries vs. testes) are independently manipulated to yield four experimental groups (Arnold & Chen, 2009; Arnold et al., 2023; Quinn et al., 2007). Prior to behavioral testing, the animals can be gonadectomized to eliminate any potential influence of circulating gonadal steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to determine whether organizational effects of gonadal steroid hormones and/or sex chromosome gene expression differences contribute to the increased female vulnerability in aELS‐induced fear learning in adulthood. One compelling approach to addressing this question would be to use the four‐core genotype rat or mouse model, where chromosomal sex (XX vs. XY) and gonadal hormone status (ovaries vs. testes) are independently manipulated to yield four experimental groups (Arnold & Chen, 2009; Arnold et al., 2023; Quinn et al., 2007). Prior to behavioral testing, the animals can be gonadectomized to eliminate any potential influence of circulating gonadal steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Sex chromosome genes have garnered attention in recent years for their potential roles in driving sex-specific differences in behavior and susceptibility to various conditions. Research involving mouse models with differing sex chromosome complements (XX, XY) and gonadal sex such as the four Core Genotypes mice has provided valuable insights (Corre, Friedel et al 2016, Arnold 2020, Ghosh, Chen et al 2021, Arnold, Chen et al 2023, Cioffi, Grassi et al 2024.…”
Section: Discussionmentioning
confidence: 99%
“…These models allowed scientists to differentiate the impacts of sex chromosomes themselves from the influence of gonadal hormones (Corre, Friedel et al 2016, Ghosh, Chen et al 2021, Arnold, Chen et al 2023, Cioffi, Grassi et al 2024. Using these models, Sneddon et al showed in a recent study that chromosomal sex plays a role in shaping the development of binge-like alcohol consumption and aversion-resistance drinking in females (Sneddon, Rasizer et al 2022, Sneddon, Masters et al 2023.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations